THE GUIDED DISCOVERY LEARNING TO IMPROVE STUDENTS’ LEARNING MOTIVATION AND CONCEPT MASTERIES OF COLLOID SYSTEM - Ade Maria Novita; Chansyanah Diawati; Noor Fadiawati (Universitas Lampung, 2012)
The observation results showed that the average marks for colloid system material of students in classroom XI IPA 1 in State Senior High School 3 in Bandar Lampung in academic year 2009-20010 was 62.56. The determined minimum accomplishment criteria (or KKM) for chemistry subject in all classrooms XI IPA was 68. Students’ motivations in learning chemistry were low. This could be seen from irrelevant students’ activities to learning such as doing other tasks, sleeping and chatting. One of efforts to improve students’ learning motivations and concept masteries in colloid system material is by implementing guided discovery learning. The objective of this research is to improve percent of students’ learning motivation and concept mastery averages with guided discovery learning. This was a classroom action research and conducted in two cycles. Research data were data of students’ learning motivation obtained from observation sheets and data of concept mastery obtained from formative tests. The results showed that there were improvements of averages of students’ learning motivations (46.92%) and concept masteries (13.87%) from cycle I to cycle II. Keywords : guided discovery learning, students’ learning motivations, concept masteries